Repeatability, reproducibility and sequential use of condition scoring of Bos indicus cattle - Nicholson, M.J.; Sayers, A.R. (Springer, 1987)
Assesses the repeatability and reproducibility of a condition scoring system. Presents results from an analysis of sequential condition scoring of cattle over a dry season to show differences between treatments and trends over time.